Types of Endorsers and its Effect on Consumer Behavior of Convenience Goods (Case study: Student in Palembang, Indonesia) - Eko Fitrianto; Islahuddin Daud; Welly Nailis (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2017)
Research objective – There are four main types of endorsers that can be used to deliver marketing communications, the types are: celebrities, ordinary people, expert, and corporate president. Each type has its own characteristics and selecting the right type endorser can influence consumer behavior on using productDesign/Metodhology/Approach – There are three factors used to test the effect of endorsers, namely: attractiveness, trustworthiness and expertise. This study is conclusive research by collecting primary data from 100 participants. Each participant was involved is the user of product and knowing every ad starring by endorser that using in this research. We use SEM analysis as technique to examine the effect between types of endorsers and consumer behavior.Findings – There is a different result on each type of endorser and its effect to their consumer behavior. On the attractiveness factor, only CEO type has affected (sign 0.008). While on trustworthiness factor, all factor has affected with expert type has the highest impact (0.016). And last, on the expertise factor, none of type of endorser that influence consumer behavior.Limitation – This research focused on how the consumer responds the ad at convenience goods. In consumer goods, emotional response caused by endorser more possible. Further research needs to explore how the consumer responds to shopping goods.Originality/value – This study compares four different types of endorsers, in which each endorser has its own characteristics, and is associated with consumer behavior